PI3K/Akt promotes GRP78 accumulation and inhibits endoplasmic reticulum stress-induced apoptosis in HEK293 cells - Dai, R. Y; Chen, S. K; Yan, D. M; Chen, R; Lui, Y. P; Duan, C. Y; Li, J; He, T; Li, H (Folia biologica (Praha), 2010)
The potential pro-survival role of phosphatidylinositol 3-kinase (PI3K)/Akt during endoplasmic reticulum stress has been well-characterized. However, the detailed mechanisms remain largely unknown. Here, we showed that PI3K/Akt inhibition promoted endoplasmic reticulum stress-induced apoptosis in a glucose-regulated protein 78 (GRP78)-dependent manner. During endoplasmic reticulum stress, high levels of Akt phosphorylation were sustained for at least 18 h in HEK293 cells. Importantly, PI3K/Akt enhanced GRP78 accumulation through increasing its stability following endoplasmic reticulum stress. Furthermore, Akt1, but not Akt2 or Akt3, was involved in GRP78 stability regulation. These results suggest that PI3K/Akt inhibits endoplasmic reticulum stress-induced apoptosis in HEK293 cells, at least in part, by promoting GRP78 protein stability.
Keywords: proteiny teplotního šoku; Stress, Physiological; transkripční faktor CHOP; zvířata; fosfatidylinositol-3-kinasy; lidé; Transcription Factor CHOP; fyziologický stres; Enzyme Inhibitors; Phosphatidylinositol 3-Kinases; thapsigargin; Mice; Thapsigargin; Endoplasmic Reticulum; myši; inhibitory enzymů; Proto-Oncogene Proteins c-akt; NIH 3T3 Cells; Humans; Cell Line; Heat-Shock Proteins; buněčné linie; Apoptosis; Animals; endoplazmatické retikulum; apoptóza; dithiothreitol; protoonkogenní proteiny c-akt; Dithiothreitol; buňky NIH 3T3